Performing crisis to create your enemy: Europe vs. the EU in Hungarian populist discourse - Sata, Robert (Frontiers in Political Science, 2023)
Hungary has become the leader of democratic backsliding within Europe, with Prime Minister Viktor Orbán turning into the staunchest critic of the EU, despite a consistent support for the European project among the wider public and Hungary being a net benefiter of EU membership. Using a systematic analysis of all speeches, statements and interviews of the PM for his three consecutive governments 2010–2022, I claim the radicalization of this Eurosceptic discourse is a direct consequence of a continuous populist performance of crisis that demands the creation of images of friends and foes to unite and mobilize people. Orbán relies on discursive processes of othering to construct to his liking both “the good people” and its enemies, who are to be blamed for the crises. Anybody can become an enemy in the various crises that follow each other. At the same time, discursive conceptions of Europe vs. the EU remain in the center of the discourse to establish Hungary's European belonging as well as opposition to EU for policies that allegedly people reject. While the economic crisis pits an economic “us” against the former socialist political elite, foreign capital, and the EU and IMF that are all blamed for Hungary's near-bankruptcy situation. The refugee crisis redefines both “us” and “others”, the “self” is distinguished using ethno-linguistic criteria and identitarian Christianity to signal the cultural distance from the Muslim migrant “other” as well as multicultural EU. The pandemic crisis is performed only to further exacerbate the conflict between the illiberal “self” and the liberal “others”, where supranational EU, promoting multiculturalism, gender ideology or neoliberal policies not only threatens the very existence of traditional-national lifestyles but endangers the people themselves. With each crisis performed, newer and newer conflict lines between various “European self's” and “threatening EU” are identified, each adding to the radicalization of Orbán's discourse. The demonization of the EU and the pretext of saving Europe using these false discursive constructs enables Orbán strengthen his grip of power and drift to authoritarianism.